Letter from the editor (2013)
Dear readers and contributors of the Earth Sciences Research Journal,Thanks again to be part of this interesting professional journal. With pretty proud I want to present this new issue (17:1, June-2013) with interesting research products coming from Antarctic continent,Mexico, Botswana, India, Turkey, Nigeria and Iran. Currently, ESRJ is covered in the top scientificIndex and Bibliographic Database as Academic Search Complete, DOAJ, Fuente Académica, GeoRef,Scopus, ISI web of Knowledge, Latindex, SciELO, Ulrich, Publindex, e-Revistas, and Academic One-file. And we expect in the future turn into one of the most referred journal in this field of knowledge...